2017
DOI: 10.28982/josam.347952
|View full text |Cite
|
Sign up to set email alerts
|

Possible cause underlying gastric necrosis and perforation: Celiac artery thrombosis

Abstract: In this article, we are sharing a case of a 76-year-old woman with known hypertension, atrial fibrillation, diabetes mellitus, coronary artery disease, who is presenting with stomach necrosis and perforation possibly due to celiac artery thrombosis after newly developed abdominal pain and bloody vomiting. In our case, emergency surgery was planned and the patient refused the operation and was lost at 48 hours of clinical follow-up. We aimed to discuss the etiology of celiac artery thrombosis, briefly. We belie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Population studies have suggested that the prevalence of coeliac axis thrombosis is between 1% and 12.5% in the general population 7. Coeliac axis thrombosis is mostly observed in patients with atherosclerosis, smoking, coagulation disorders, connective tissue diseases and congenital abnormalities 8. As the thrombosis occurs at the origin of the coeliac artery, it can cause widespread ischemia of liver, bowel and spleen 9…”
Section: Introductionmentioning
confidence: 99%
“…Population studies have suggested that the prevalence of coeliac axis thrombosis is between 1% and 12.5% in the general population 7. Coeliac axis thrombosis is mostly observed in patients with atherosclerosis, smoking, coagulation disorders, connective tissue diseases and congenital abnormalities 8. As the thrombosis occurs at the origin of the coeliac artery, it can cause widespread ischemia of liver, bowel and spleen 9…”
Section: Introductionmentioning
confidence: 99%